Speaking Success: Integrating Islamic Values In English Clubs For Future Language Teacher Students - Sholikhi, Fu'ad; Primasari, Yusniarsi; Hasanah, Oktavia Dwi (Yayasan Indonesia Emerging Literacy Education, 2025)
The integration of Islamic values into extracurricular activities offered by English institutions of higher education is a salient issue in the context of Islamic higher education. The objective of this study is to examine the implementation of Islamic values in the English Club, with the aim of enhancing the speaking skills of prospective English teachers at Balitar Islamic University. This study is significant because it aims to maximize students' character development while simultaneously overcoming the challenges associated with incorporating spiritual concepts into the context of teaching foreign languages. The research method used a qualitative case study methodology, with data collected through semi-structured interviews and observational investigations of ten participants. The data was analyzed by reducing it, with a focus on the realm of competency in the discipline. The data was presented in the form of a theme table, and the results were based on the validation of two teachers. And the findings imply that the English club’s environment promotes learning and confidence in public speaking. Students are drawn in by the club's audiovisual resources, Islamic teaching techniques, and practical approach, which also positions it as a reliable resource for academic and professional development.